Pengaruh Metode Latihan dan Kemampuan Motorik terhadap Hasil Belajar Sepakbola - Hady Suyono dkk Hady Suyono dkk (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2001)
The Effect of Exercise Methods and Motoric Abilities on Learning Outcomes in Football. This experimental study was designed to examine the effect of exercise methods on learning outcomes in football course attended by students with different motoric abilities. It involved 40 students of State University of Medan (Unimed) selected purposively. The study applied BMA Test to test students' motoric abilities and the AAHPER Football Test to identify their learning outcomes. Analyses of variance and t-test were used to analyse the data. It was found out that there was no difference in learning outcomes between the students attending physical exercise and those attending mental and physical exercise combined. Students with high motoric abilities gained higher achievement by physical exercise than those attending mental and physical exercise combined.